2021
DOI: 10.1021/acs.jpclett.1c02121
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Correlation between the Nanoparticle and the Growing Au-Assisted InxGa1–xAs Nanowire

Abstract: The nanowire geometry is favorable for the growth of ternary semiconductor materials, because the composition and properties can be tuned freely without substrate lattice matching. To achieve precise control of the composition in ternary semiconductor nanowires, a deeper understanding of the growth is required. One unknown aspect of seeded nanowire growth is how the composition of the catalyst nanoparticle affects the resulting composition of the growing nanowire. We report the first in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…However, if the self-regulating effect occurs, this can be an explanation for why InGaAs nanowires can grow in any composition within the miscibility gap of the system. 10 We have also shown that multilayers can emerge in conjunction with the formation of a sharp heterostructure. This is of course a much larger perturbation to the system than a small change in composition or a crystallographic twin, so it is reasonable to assume that the effect is larger.…”
Section: ■ Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…However, if the self-regulating effect occurs, this can be an explanation for why InGaAs nanowires can grow in any composition within the miscibility gap of the system. 10 We have also shown that multilayers can emerge in conjunction with the formation of a sharp heterostructure. This is of course a much larger perturbation to the system than a small change in composition or a crystallographic twin, so it is reasonable to assume that the effect is larger.…”
Section: ■ Discussionmentioning
confidence: 67%
“…The nanoparticle composition was also measured before and after the multilayer growth, which revealed that the nanoparticle composition was more consistent, with Ga < 3 atom % and In > 40 atom %, similar to earlier in situ studies of In x Ga 1−x As growth. 10 In order to learn more about the implications this multilayer growth has on the evolution of the nanowire, the layer propagation times of the individual layers were studied further. Figure 4 shows the layer propagation time of individual layers as a function of the average number of layers that grow simultaneously during the growth of said layer.…”
Section: Dynamics Of Multilayer Stacksmentioning
confidence: 99%
See 2 more Smart Citations
“…A common topic for discussing the growth of ternary III–V nanowires, using InGaAs as a model system, is the miscibility gap. The miscibility gap exists for the bulk system, and because of this, it is a naturally emerging result of many thermodynamic models for predicting the nanowire composition. ,, However, experimentally grown nanowires have shown compositions within the miscibility gap. ,, This calls into question what suppresses the miscibility gap in experimental growth, and one potential candidate would be strain. For bulk systems consisting of (pseudo)­binary materials with a large mismatch (like the InAs–GaAs system), strain can lead to narrowing of the miscibility gap and prevention of spinodal decomposition in these materials systems. , However, strain is difficult to capture in conventional steady state models, since strain has no effect if the composition of the solid is always constant.…”
Section: Introductionmentioning
confidence: 99%